The maqasid-guided medical decision making: the case of covid-19 pandemic - Shogar, Ibrahim Adam Ahmed; Bendebka, Ramzi; Mohd Yusof, Nazri (2022)
The investigation on decision theory, over the course of last few decades, has afforded constructive findings, profound insights and practical descriptions on this topic. The discussion on the matter has posted fundamental questions about the rational bases, principles, standards, models and techniques for optimal choice that influence the decision making in various fields of the practical life, ranging between public administration, law and economic, to educational and medical decision. This work aims to investigate contribution of Maqāṣid theory as a mechanism for choice in the process of medical decision making, with emphasis on COVID-19 case. It is a serious attempt to understand Maqāṣid theory in the context of the general theory of decision making, comparatively with needs theory. The article presupposes that Maqāṣid al-Shariah, i.e., the final objectives of Islamic law, can play an important role in the process of medical decision, both as a medical research and clinical practice. To examine this central presupposition the paper analyzes, in four basic parts, fundamentals of the general theory of decision making, tools and techniques of the optimum decision, the framework of Maqasid-based medical decision and its applications. Decision making, in this context, is defined as “the optimum choice between alternative courses of action”. The paper has concluded that although the Maqāṣid theory was designed and developed for the legal decision making, nevertheless its principles are applicable to all modes of decision making, such as administrative, educational, medical and clinical decision which is closely related to the five final objectives of Islamic legal decision. Maqāṣid theory contributes in optimal medical decision through promotion of its two components which are source of knowledge and method of judgment. Through analyzing modes of human needs and hierarchies of the interest (Maslaha), Maqāṣid theory provides the ethico-legal framework for optimum medical decision.